2017
DOI: 10.3390/catal7020049
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Thermostable Lipase QLM on Core-Shell Structured Polydopamine-Coated Fe3O4 Nanoparticles

Abstract: Abstract:Here, core-shell structured polydopamine-coated Fe 3 O 4 nanoparticles were constructed to immobilize thermostable lipase QLM from Alcaligenes sp. Systematical characterization indicated that lipase QLM was successfully immobilized on the surface of nanoparticles with an enzyme loading of 21.4 ± 1.47 mg/g immobilized enzyme. Then, the immobilized enzyme was demonstrated to possess favorable catalytic activity and stability in the ester hydrolysis, using p-nitrophenyl caprylate as the substrate. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Enzyme was first immobilized on magnetic nanoparticles surface by Matsunaga and Kamiya [17]. Immobilizing lipase on magnetite will generate a nano-biocatalyst, which will grant the edge of better activity in harsh conditions and reusability [18].…”
Section: Introductionmentioning
confidence: 99%
“…Enzyme was first immobilized on magnetic nanoparticles surface by Matsunaga and Kamiya [17]. Immobilizing lipase on magnetite will generate a nano-biocatalyst, which will grant the edge of better activity in harsh conditions and reusability [18].…”
Section: Introductionmentioning
confidence: 99%
“…PDA‐coated magnetic nanoparticles with immobilized lipase QLM from Alcaligenes sp . with a loading of 21.4±1.47 mg g −1 was applied in the hydrolysis of 4‐nitrophenyl caprylate . The immobilized enzyme showed a better tolerance to temperature but exhibited significant activity decreases during eight reuses with a remaining activity of 10 %.…”
Section: Immobilized Enzymes As Catalystsmentioning
confidence: 99%
“…Remarkably, ABS materials for enzyme immobilization still face several problems, including low loading efficiency and poor catalytic performance in practice. Mussel-inspired surface chemical modifications are of great interest due to their simplicity, versatility, and wide applicability. , Polydopamine, with a unique ability to form a surface coating layer that contains catechol, amine, and quinone functional groups, can be used in numerous biological reactions. Previous studies have also demonstrated that immobilizing enzymes through polydopamine is a practical and efficient strategy for obtaining high enzyme loads, favorable activity, stability, and reusability. The most common strategy to polymerize dopamine into polydopamine is performing autopolymerization through oxygen oxidation under alkaline conditions. However, such a strategy tends to generate catechol dimers that cannot form covalent bonds with amino or thiol groups and are consequently detrimental to enzyme immobilization. , In contrast, performing electro-oxidation with dopamine ensures that the main product is dopaquinone.…”
Section: Introductionmentioning
confidence: 99%